Transcranial near-infrared laser improves postoperative neurocognitive disorder in aged mice via SIRT3/AMPK/Nrf2 pathway - Zhong, Junying; Zhao, Le; Wu, Wensi; Chen, Jiawei; Yuan, Shangyan; Zhang, Xiaojun; Wang, Zhi (Frontiers in Neuroscience, 2023)
Background Postoperative neurocognitive disorder (PND) is a common central nervous system (CNS) complication that might increase the morbidity and mortality of elderly patients after anesthesia/surgery. Neuroinflammation, oxidative stress, and synaptic dysfunction are closely related to cognitive dysfunction, an important clinical feature of PND. Transcranial near-infrared laser (TNIL) is regarded as an effective treatment for cognitive-related diseases by improving mitochondrial function and alleviating neuroinflammation and oxidative stress damage. Materials and methods Aged male C57BL/6 mice underwent a carotid artery exposure procedure under isoflurane anesthesia. We treated PND-aged mice for three consecutive days (4 h post-operation, 1-laser) with 810 nm continuous wave (CW) laser 18 J/cm2 at 120 mW/cm2. The post-treatment evaluation included behavioral tests, RTq-PCR, immunofluorescence, and Western blot. Results The results demonstrated that TNIL improved PND and the levels of synaptic function-associated proteins such as post-synaptic density protein 95 (PSD95), synaptophysin (SYP), and brain-derived neurotrophic factor (BDNF). Besides, neuroinflammatory cytokine levels of tumor necrosis factor (TNF)-α and interleukin (IL)-1β as well as microglia activation and oxidative stress damage were attenuated after TNIL treatment in aged mice with PND. Further investigation suggested that TNIL relieved oxidative stress response by activating the SIRT3/AMPK/Nrf2 pathway. Conclusion Transcranial near-infrared laser improved cognitive impairment in aged mice with PND, which may be a promising therapeutic for PND.